DELINEATION OF GROUNDWATER CONTAMINATION USING ELECTRICAL METHOD AT DUMP SITE IN AWKA URBAN LOCALITY, ANAMBRA STATE, NIGERIA. - Edward, Chikwelu emenike (Universitas Negeri Semarang, 2019)
A resistivity survey was carried out to study the level of groundwater pollution in the dumpsite at Awka Urban Anambra State. Depth, thickness, resistivity, and sediment at which contamination of groundwater occurred were also established. From the analysis, the dump site has four layers, contaminated topsoil, subsoil, rock fragment, and bedrock while the control side has four layers also which are, topsoil, subsoil, rock fragment, and bedrock. The effect of leachates can be seen at the dump site, the first layer (contaminated topsoil) with low resistivity values and this effect tends to affect some distance at the second layer (subsoil). The control site has no effect of leachate which shows high resistivity values at its first and second layer compare to that of the dump site. The iso-resistivity maps also reveal the variation between the dump site and control site, at the 5 m and 10 m plot of the iso-resistivity maps, the dump site (profile A to D), shows low resistivity values compare to the control site (profile E and F). At the 12 m depth, the resistivity values at the dump site and control site tend to be at a similar range, which explains that the effect of leachate disappears at 12 m depth. At 20 m depth, the resistivity values at the control site (Western side of the map) is lower than that of the dump site which could explain the effect of water-bearing materials or weathering of the rocks at that depth.